PENGARUH PENDIDIKAN KARAKTER TERHADAP PERILAKU SISWA - Halawati, Firda (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
This study aims to determine (1) How is student character education (2) How is student behavior, (3) is there any influence of character education on student behavior. This research uses quantitative research with survey research type. The population of this study were all 112 Sindangjawa MI students. The sampling technique using simple random sampling obtained a sample of 88 students. Data collection techniques using questionnaire instruments, observation and documentation. The measuring instrument used was a questionnaire, the analysis of the instruments included validity and reliability test analysis. Data analysis is in the form of simple linear regression analysis and correlation test. Prior to the analysis, the prerequisite tests are normality test, homogeneity test and autocorrelation test. The results of this study indicate that (1) Student character education is very high with a percentage of 88.64%, (2) Student behavior shows a very good category of 77.27%, (3) There is a positive influence between character education on student behavior. Where if student character education increases by 1%, it will also be followed by an increase in student behavior by 0.471. In the f test, the fcount of 4.483 was obtained and the significance level of the significance level of 5% was 3.39. Based on the results of regression analysis, the value of r is 0.446 and r2 is 0.526. This means that the influence of character education on student behavior by 52.6%, while the rest is influenced by other factors outside the variables in this study.